Environmental Impact Assessment Review - Environmental Impact Assessment Review (Elsevier, 2026)
Environmental Impact Assessment Review (EIA Review) is a refereed, interdisciplinary journal serving a global audience of practitioners, policy-makers, regulators, academics and others with an interest in the field of impact assessment (IA) and management. Impact assessment is defined by the International Association for Impact Assessment (www.iaia.org) as the process of identifying the future consequences of a current or proposed action.
FI 2.16
Q1
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Evaluación del ciclo de vida; Huella de carbono; Análisis energético